2020
DOI: 10.1111/jocs.15118
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation bridge to heart transplant: Trends following the allocation change

Abstract: Background: This study compared outcomes of patients bridged with extracorporeal membrane oxygenation (ECMO) to orthotopic heart transplantation (OHT) following the recent heart allocation policy change. Methods: The United Network of Organ Sharing Registry (UNOS) database was queried to examine OHT patients between 2010 and 2020 that were bridged with ECMO. Waitlist outcomes and 1-year posttransplant survival were compared between patients waitlisted and/or transplanted before and after the heart allocation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 14 publications
1
33
0
1
Order By: Relevance
“…Our findings expand on work by Kilic and colleagues, who found improved waitlist outcomes but similar post-transplant mortality for ECMO patients following the rule change [5].…”
Section: Plos Onesupporting
confidence: 86%
See 1 more Smart Citation
“…Our findings expand on work by Kilic and colleagues, who found improved waitlist outcomes but similar post-transplant mortality for ECMO patients following the rule change [5].…”
Section: Plos Onesupporting
confidence: 86%
“…Conversely, temporary MCS (tMCS) devices such as ECMO and IABP are increasingly used as bridge to transplantation [3,4]. While such changes in MCS use under the new system have been previously described [4][5][6][7][8], little is known regarding the characteristics and outcomes of the large influx of patients now being bridged with ECMO in the new allocation scheme. The present study characterized changes in waitlist and post-transplant outcomes of ECMO patients being bridged to transplantation following the 2018 OPTN policy change.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study was performed by Hess et al who demonstrated a higher likelihood of HT in patients supported with ECMO in the new allocation system and a marked reduction in median waitlist time from 47 to four days. The authors established comparable one-year survival rates in the new and old system (new 79.8% vs. old 90.3%; p = 0.3917), with equivalent rates of stroke and one-year acute rejection, although postoperative renal failure was significantly higher in the new policy group [ 22 ]. Several other studies reported significant improvement in post-transplant survival, a lower hazard of post-transplant mortality, a lower rate of waitlist mortality, and an up to 50% reduced waitlist time after implementation of the new system (from 11 or 10 days vs. five days) [ 23 , 24 ], as well.…”
Section: Ecmo As a Bridge To Ht Strategy In Different Allocation Syst...mentioning
confidence: 99%
“…The reasoning for this is unclear given the limitations of the UNOS database. While donor organ allocation status changes in 2018 have affected strategies of bridging patients to transplant with both durable and temporary mechanical circulatory support, the TAH continues to have Status 2 allocation in the new scheme so this should not have necessarily decreased transplant offers 10,11. What the change in allocation strategy did affect as demonstrated by our study was the waitlist time for TAH BTT therapy, which was significantly shorter in the TAH population after 2018.…”
mentioning
confidence: 73%